Triage Knowledge of Emergency Rooms Nurses at Dr Soetomo Regional General Hospital - Fariza Nur Aini Widyani; April Poerwanto Basuki; Djohar Nuswantoro (Faculty of Medicine-Universitas Airlangga, 2020)
Introduction: Triage is a system to sort patients based on their urgency for care during an emergency. In addition, to determine patient's severity, triage reduces time wasted and overcrowding in the emergency room.1 Triage errors such as over-triage or under-triage must not exceed 35% and 5% of the total numbers of patients respectively. Dr. Soetomo General Hospital of Surabaya with its status as one of type